Graphic Guide System And Evaluation Model Based On User Experience - Xiong Ding; Teddy Marius Soikun (Webology Center, 2021)
The design of a graphic guidance system based on a people-oriented and user experience perspective is a new research field. The UX (User Experience) approach to design the guidance system is a combination of the five elements of UX by Garrett. This study explains the related UX problems in the graphic guide system design and tries to find the best solution to design the system laws. Questions: This study mainly explores two aspects. First, create a theoretical framework of the graphic guide system from the perspective of UX. Secondly, build a guide system evaluation model based on UX. Methodology: 1. Develop a theoretical framework for a guidance system dominated by UX using theoretical research and review methods. 2. Using the AHP (the Analytic Hierarchy Process) method and combining it with Nanning public transport station case study, the priority levels of the guidance system are arranged first from the five levels of UX. Then the AHP method is used to standardize the evaluation data of the fivelayer frame. Subsequently, the priority weight of 19 index layers of the five decision-making levels is sorted, and the results are obtained. Finally, it summarizes the excellent graphic guide system design and evaluation model system centered on UX. It provides a reference for scientific and accurate methods and ideas for future graphic guide system design and evaluation.